Faktor Yang Mempengaruhi Minat Masyarakat Dalam Pemanfaatan Home Care Di Puskesmas Layang - Muliany, Andi Any; Arman, Arman; Ahri, Reza Aril (Window of Health : Jurnal Kesehatan, 2018)
This research is based on because the utilization of home care in Clinics Layang unlike others clinic in Makassar city. Many factors being the cause of a lack of Community interest in the utilization of home care Clinics in the region Kites. So this research aims to identify the factors that influence people's interest in the utilization of home care in the clinic Layang, besides this research aims to analyze the influence of socialization, the environment, facilities services and image in the utilization of home care in Clinics of the overpass. This research using quantitative research approach to an analytic survey. Sample research as much as 92 people, namely people who are domiciled in the territory of the health workers and utilize Your facilities services home care at least 2 visits. Data collection techniques using questionnaires and observation. The results showed that the variables affecting people's interest in the socialization of the utilization of home care are not significant with the value of the sig = 0.097, residence environment variables affect people's interest in the utilization of home care are not significant with the value of the sig = 0.417, variable service facility affect people's interest in the utilization of home care are not significant with the value of the sig = 0.235, and image variables affect people's interest in the utilization of home care are not significant with the value of the sig = 0.133. In conclusion, the four variables examined, socialization variables, environment, facilities services and image have no significant influence on the people's interest in the utilization of home care.